2013
DOI: 10.1016/j.paid.2013.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Personality trait change and life satisfaction in adults: The roles of age and hedonic balance

Abstract: This paper examines whether changes in personality traits influenced life satisfaction (LS). This involved investigating whether these associations were moderated by age and mediated by hedonic balance (i.e., positive and negative affect). Participants included 11,104 Australian adults aged 18-79. years, with data available from two time points (baseline and 4-year follow up). Latent difference score modeling indicated that increased neuroticism was associated with lower LS, whereas increased extraversion, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 29 publications
3
47
0
1
Order By: Relevance
“…This construct refers to the balance of positive and negative emotions, measured as the difference between the two. Some studies addressed the association between hedonic balance and other well-being-related constructs, such as life satisfaction [66]. Furthermore, hedonic balance may account for job-related well-being and job satisfaction.…”
Section: Teachers' Emotions and Hedonic Balancementioning
confidence: 99%
“…This construct refers to the balance of positive and negative emotions, measured as the difference between the two. Some studies addressed the association between hedonic balance and other well-being-related constructs, such as life satisfaction [66]. Furthermore, hedonic balance may account for job-related well-being and job satisfaction.…”
Section: Teachers' Emotions and Hedonic Balancementioning
confidence: 99%
“…On the other hand, a positive relationship was observed between the agreeableness trait and life satisfaction in many studies (including Magee et al, 2013). [44] Therefore, it could be concluded that women within the age range of 20-30 years have higher levels of agreeableness and life satisfaction compared to men at the same age.…”
Section: Discussionmentioning
confidence: 97%
“… career choices (Ackerman & Beier, 2003;Eley, Eley, Bertello, & Rogers-Clark, 2012;Holland, 1997;Jones et al, 2013;Malhi et al, 2011),  career satisfaction (Richardson, Lounsbury, Bhaskar, Gibson, & Drost, 2009)  life satisfaction Josefsson et al, 2011;Magee, Miller, & Heaven, 2013).…”
Section: Temperament and Character Inventory (Tci)mentioning
confidence: 99%
“…The reasons for observed personality differences across generational cohorts has been debated (Robbins et al, 2010), with some concluding that changes in the sociocultural context, particularly cultural shifts in child-raising norms, are responsible (Smits, Dolan, Vorst, Wicherts, & Timmerman, 2011;Twenge, 2009). However, a systematic review of the literature on adult personality identified that personality change does occur during adulthood (Helson et al, 2002), with age moderating trait expression (Magee et al, 2013). Using Dweck's (2008) perspective, maturation impacts personality such that biological tendencies are modified by the experiences, beliefs and goals of individuals.…”
Section: Trait Approachesmentioning
confidence: 99%
See 1 more Smart Citation